Intact working memory in the absence of forebrain neuronal glycine transporter 1 - Dubroqua, Sylvain (2012)
Glycine transporter 1 (GlyT1) is a potential pharmacological target to ameliorate memory deficits attributable to N-methyl-d-aspartate receptor (NMDAR) hypofunction. Disruption of glycine-reuptake near excitatory synapses is expected to enhance NMDAR function by increasing glycine-B site occupancy. Genetic models with conditional GlyT1 deletion restricted to forebrain neurons have yielded several promising promnesic effects, yet its impact on working memory function remains essentially unanswered because the previous attempt had yielded un-interpretable outcomes. The present study clarified this important outstanding lacuna using a within-subject multi-test approach. Here, a consistent lack of effects was convincingly demonstrated across three working memory tests - the radial arm maze, the cheeseboard maze, and the water maze. These null outcomes contrasted with the phenotype of enhanced working memory performance seen in mutant mice with GlyT1 deletion extended to cortical/hippocampal glial cells. It follows that glial-based GlyT1 might be more closely linked to the modulation of working memory function, and raises the possibility that neuronal and glial GlyT1 may regulate cognitive functions via dissociable mechanisms.